SUFI IDENTITY IN MAWLID SYARAFAL ANAM POETRY - As. Rakhmad Idris (Pusbindiklat - LIPI, 2015)
Arabian poetry reading has still continued in the religious tradition in Indonesia. The poetry which is usually read in this tradition are about praise poetry to The Prophet Muhammad S.A.W. One of them are Mawlid Syarafal Anam (MSA), but the reading has not been balanced with the comprehension of the meaning and main aim of the poetry. Despite the less comprehension, the poet wanted the reader can understand and interprete the meaning in every each verse. This study will analyze the words and sentences in MSA which is identified the representation of sufi identify. The aim in this paper is to reveal sufi identity which is represented in words and sentences. The society of MSA is expected to have a new knowledge about sufi identity which is describe in this paper. The method using to identify the sufi identity is the descriptive one. The data is collected by classified the words and sentences which has identify the sufi in MSA. The data then are analyzed by qualitative approach based on identity theory of Stuart Hall. The result of analysis based on the collected data shows that there is sufi identity in the poet of MSA. The identity is clearly shown by the words and sentences about ahwal, one of sufi thought. There are three ahwal: longing, devotion, (both are to Allah and the Prophets), and introspection. Those ahwal in MSA make this poetry are unique than the other.